current status and management of South Africa's chondrichthyan fisheries - da Silva, C; Booth, AJ; Dudley, SFJ; Kerwath, SE; Lamberth, SJ; Leslie, RW; McCord, ME; Sauer, WHH; Zweig, T (African journal of marine science, 2015)
Chondrichthyans (sharks, skates, rays and chimaeras) are captured in many marine fisheries. Management and research efforts directed at chondrichthyan fishing are often neglected because of low product value, taxonomic uncertainty, low capture rates, and harvesting by multiple fisheries. In South Africa's diverse fishery sectors, which include artisanal as well as highly industrialised fisheries, 99 (49%) of 204 chondrichthyan species that occur in southern Africa are targeted regularly or taken as bycatch. Total reported dressed catch for 2010, 2011 and 2012 was estimated to be 3 375 t, 3 241 t and 2 527 t, respectively. Two‑thirds of the reported catch was bycatch. Regulations aimed at limiting chondrichthyan catches, coupled with species‑specific permit conditions, currently exist in the following fisheries: demersal shark longline, pelagic longline, recreational line, and beach‑seine and gillnet. Limited management measures are currently in place for chondrichthyans captured in other South African fisheries. Catch and effort dataseries suitable for stock assessments exist for fewer than 10 species. Stock assessments have been attempted for five shark species: soupfin Galeorhinus galeus , smoothhound Mustelus mustelus , white Carcharodon carcharias , spotted ragged‑tooth Carcharias taurus , and spotted gully Triakis megalopterus . Fishery‑independent surveys and fishery observer data, which can be used as a measure of relative abundance, exist for 67 species. Compared with most developing countries, South African shark fishing is relatively well controlled and managed. As elsewhere, incidental capture and bycatch remain challenges to the appropriate management of shark species. In 2013, South Africa's National Plan of Action for the Conservation and Management of Sharks (NPOA‑Sharks) was published. Implementation of the NPOA‑Sharks should help to improve chondrichthyan management in the near future.